The Effect of Application of E-SKP and Competency Assessment System, On Performance with Work Discipline as an Intervening Variable in Papua Province Forestry and Environmental Services - Nugroho, Yohanes H. Bambang A.; Christian, Ferdinandus; Sardjiyo, Sardjiyo (Technium Social Sciences Journal, 2023)
The aim of the study was to determine the effect of the application of the E-SKP assessment system and competence on performance with work discipline as an intervening variable in the Forestry and Environment Service of Papua Province. This is a quantitative study with 109 respondents. The results of the questionnaire were tabulated and analysed using Structural Equation Modelling (SEM) using the Smart PLS application. The results of the study are that E-SKP has a positive and significant effect on employee performance and work discipline. Work discipline does not mediate the relationship between E-SKP and employee performance. Competence has a positive and significant effect on employee performance. Employee work discipline. Work discipline does not mediate the relationship between competence and pawnshop performance. Work discipline has a negative and insignificant effect on the performance of employees of the Papua Province Forestry and Environment Service employees.